2003
DOI: 10.1046/j.1365-2958.2003.03877.x
|View full text |Cite
|
Sign up to set email alerts
|

Genes involved in matrix formation in Pseudomonas aeruginosa PA14 biofilms

Abstract: SummaryPseudomonas aeruginosa forms diverse matrixenclosed surface-associated multicellular assemblages (biofilms) that aid in its survival in a variety of environments. One such biofilm is the pellicle that forms at the air-liquid interface in standing cultures. We screened for transposon insertion mutants of P. aeruginosa PA14 that were unable to form pellicles. Analysis of these mutants led to the identification of seven adjacent genes, named pel genes, the products of which appear to be involved in the for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
745
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 692 publications
(786 citation statements)
references
References 68 publications
(123 reference statements)
24
745
1
2
Order By: Relevance
“…As a result, this screen has enabled identification of biofilm determinants that we might not have detected using the crystal violet assay. Consistent with our findings in V. parahaemolyticus, a pellicle screen was recently implemented in Pseudomonas aeruginosa PA14 to discover new genetic determinants involved in the production of a carbohydrate containing extracellular matrix component (Friedman and Kolter, 2004).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…As a result, this screen has enabled identification of biofilm determinants that we might not have detected using the crystal violet assay. Consistent with our findings in V. parahaemolyticus, a pellicle screen was recently implemented in Pseudomonas aeruginosa PA14 to discover new genetic determinants involved in the production of a carbohydrate containing extracellular matrix component (Friedman and Kolter, 2004).…”
Section: Discussionsupporting
confidence: 64%
“…This medium has been used to detect cell surface appendages, extracellular matrix production, A- layer proteins, and as an indicator of virulence (Kay et al, 1985;Collinson et al, 1993;Romling and Rohde, 1999;Romling et al, 2000;Zogaj et al, 2003;Friedman and Kolter, 2004). OP or TR parental strains have rough colony morphologies when grown on Congo red medium (Fig.…”
Section: Pellicles With Subtle Defects Have Lesions Causing Altered Cmentioning
confidence: 99%
“…Similar results were obtained using a mutant derivative of the nonmucoid strain P. aeruginosa PAO1 engineered to overproduce alginate (25,60). On the other hand, results using wild-type P. aeruginosa PAO1 and PA14 showed that alginate was not associated with biofilms (72) and that a second polysaccharide likely encoded by a separate polysaccharide biosynthetic gene cluster may provide the extracellular matrix material for those cells (18,19,29). In another report, using P. aeruginosa PAO1, DNA was suggested to be the extracellular matrix material, since the addition of DNase to biofilms dispersed the bacteria (64).…”
supporting
confidence: 69%
“…A recent study describing the EPS of PAO1 biofilms identified the major carbohydrate moieties in this to include glucose, rhamnose, mannose, xylose, 3-deoxy-D-manno-oct-2-ulosonic acid (KDO),N-acetylgalactosamine, N-acetylfucosamine, and N-acetylglucosamine (70). More recently, two genetic loci (psl and pel) responsible for the production of mannose-rich (psl) and glucose-rich (pel) polymer components of P. aeruginosa EPS (18,19,52) were identified. With the exception of KDO with its ionizable carboxylate, most of the sugars described in these studies are neutrally charged or sugars with a possible ionizable amine group (depending on polymeric linkage), which may be difficult to stain.…”
mentioning
confidence: 99%